2010
DOI: 10.1007/s00586-010-1384-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and in vivo evaluation of experimental closure devices of the annulus fibrosus designed for a goat nucleus replacement model

Abstract: Promising strategies are being developed to replace or regenerate the herniated nucleus pulposus. However, clinical efficacy of these methods has still to be addressed, and the lack of appropriate annulus closure techniques is increasingly being recognised as a major limiting factor. In the current study, in vitro and in vivo evaluation of novel annulus closure devices (ACDs) was performed. These devices are intended to be used in adjunct to nucleus replacement therapies in an experimental goat study. After a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…One could use a percutaneous procedure similar to a discogram to insert the PU mass transfer devices through the dorsal AF in discs demonstrating degeneration to attempt to arrest disc degeneration from nutrient loss. During daily living, the human lumbar spine withstands compressive loads of high magnitudes [63] which may cause migration and deformation of implanted devices [29]. In this study, no static or dynamic loading was applied to FSUs during 7 days of culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One could use a percutaneous procedure similar to a discogram to insert the PU mass transfer devices through the dorsal AF in discs demonstrating degeneration to attempt to arrest disc degeneration from nutrient loss. During daily living, the human lumbar spine withstands compressive loads of high magnitudes [63] which may cause migration and deformation of implanted devices [29]. In this study, no static or dynamic loading was applied to FSUs during 7 days of culture.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that several biomaterials implanted for closure of AF defects maintain the height and stability of the IVD [2931]. Since there are ample nutrient supplies at the edges of AF due to blood supply, porous materials with high transport properties implanted in AF can be designed to facilitate transport of nutrients from the edge of AF into the NP region in order to promote cellular energy production.…”
Section: Introductionmentioning
confidence: 99%
“…In-vivo testing of various suture techniques failed to restore healthy biomechanics better than no repair (151). Plug devices intended to retain NP fluid pressurization have failed due to mismatched compliance between the implant and surrounding tissue (152). Recently developed fibrin-genipin hydrogel adhesives with tuneable mechanical properties (Figure 6B) (153) may have the potential to fill these gaps without inducing stress concentrations in the surrounding tissue.…”
Section: How Do We Repair Ivds? Biomaterials For Repair Of the Ivdmentioning
confidence: 99%
“…The reduction in re-herniation rates was promising for a sutured AF repair, but no data was reported on disc height, biomechanical restoration of the motion segment, or MRI signal intensity providing no evidence that this technique would successfully prevent accelerated degeneration following discectomy procedures. An annulus closure plug had favorable biomechanical results in vitro but showed deformation and herniation after 6 weeks in an in vivo goat model [16]. Alternately, Barricaid is a device resembling a shield that is secured with an anchor into the adjacent inferior vertebral body to reduce the risk of tissue expulsion following a discectomy procedure (Intrinsic Therapeutics, Inc., Woburn, MA).…”
Section: Introductionmentioning
confidence: 99%